The Extent of Fault-Associated Modern Authigenic Barite Deposits Offshore Northern Baja California Revealed by High-Resolution Mapping - Gwiazda, Roberto H.; Paull, Charles K.; Caress, David W.; Preston, Christina Marie; Johnson, Shannon B.; Lundsten, Eve M.; Anderson, Krystle (Frontiers in Marine Science, 2019)
High resolution mapping with an autonomous underwater vehicle (AUV) of a section of the San Clemente fault, offshore Southern California, reveals the largest documented cold seep-associated barite deposits discovered to date. Although barite deposits along this fault, north of the mapped area, have been observed and sampled before in submersible dives, this study reveals massive newly found outcrops. The high-resolution surveys resolve their small scale morphology, their large geographical extent and the structural controls on their emplacement. Detailed bathymetry (1m x 1m x 0.25 m grid resolution) of a ~12 km2 area intersected by the fault exhibits quasi-circular mounds of 10-30 m planar dimensions rising up to 11 m above the surrounding seafloor on a 30-45 m high and at least 1,100 m long ridge, and along truncated outcropping strata, but not along the fault trace. Observations from a remotely operated vehicle (ROV) show that the mounds consist of steep sided dark-varnished blocks of barite. Active barite precipitation occurs as white friable spires emerging from the older deposits, or as white porous precipitates filling fissures. Upward thinning spires and microbial mats occurrences atop the spires are consistent with aggradational growth due to precipitation from upward flowing solutions. Live Lamellibrachia tubeworms are found in association with the fissure-filling barite precipitates. Mapping surveys were also conducted along a short section of the San Clemente fault south of the Navy Fan. In addition, a 9 km2 area along the San Diego Trough Fault south of the US-Mexico border was mapped and visited in an ROV dive. In the three mapped regions sub-bottom chirp profiles indicate that barite precipitation occurs where strata, truncated and uplifted by the fault, has thin or no sediment drape allowing for Ba-rich solutions flowing along bedding planes to mix with seawater sulfate at the seafloor interface. Despite the massive scale of the barite mounds, they are not resolvable in surface ship multibeam-generated bathymetry (25 m grid resolution). As only a few areas have been mapped at the high resolution employed in this study, the full extent of these deposits along the San Clemente Fault and other faults remains unknown.